Doxorubicin-Bound Hydroxyethyl Starch Conjugate Nanoparticles with pH/Redox Responsive Linkage for Enhancing Antitumor Therapy - Tan R (Dove Medical Press, 2021)
Ronghua Tan, Danlei Tian, Jiaoyan Liu, Congcong Wang, Ying Wan National Engineering Research Center for Nanomedicine, College of Life Science and Technology, Huazhong University of Science and Technology, Wuhan, 430074, People’s Republic of ChinaCorrespondence: Ying Wan Tel +86 27-87792147Fax +86 27-87792234Email ying_wan@hust.edu.cnBackground: Chemotherapeutic drugs used for tumor treatments often show limited efficiency due to their short lifetime, nonspecific delivery, and slow or insufficient intracellular drug release, and also, they can cause severe system or organ toxicity. The development of chemotherapeutic nanomedicines with high efficacy and satisfactory safety still remains a challenge for current tumor chemotherapy.Methods: A novel type of conjugate was synthesized using hydroxyethyl starch (HES) as a carrier while binding doxorubicin (DOX) onto HES backbone through a pH/redox responsive linker containing both disulfide and hydrazone bonds in series. The built conjugates were self-assembled into nanoparticles (NPs) (HES-SS-hyd-DOX NPs) for achieving enhanced antitumor therapy and adequate safety.Results: HES-SS-hyd-DOX NPs had a certain ability for the tumor-orientated drug accumulation and were capable of releasing DOX itself rather than DOX derivatives. It was found that the pH/redox responsive linkage enabled the NPs to achieve fast and sufficient intracellular drug release. Based on the tumor-bearing mouse model, antitumor results demonstrated that these NPs were able to inhibit the growth of the advanced tumors with significantly enhanced efficacy when compared to free DOX, and to those conjugate NPs containing only a single responsive or unresponsive bond. Besides, HES-SS-hyd-DOX NPs also showed adequate safety to the normal organs of the treated mice.Conclusion: The pH/redox responsive linkage in HES-SS-hyd-DOX was found to play a critical role in mediating the drug accumulation and the fast and sufficient intracellular drug release. The HES-exposed surface of HES-SS-hyd-DOX NPs endowed the NPs with long circulation capability and remarkably reduced the DOX-induced side effects.Keywords: hydroxyethyl starch, doxorubicin, conjugate nanoparticles, pH/redox responsive linkage, antitumor therapy